Utilization of carbon-based energy as raw material instead of fuel with low CO2 emissions: Energy analyses and process integration of chemical looping ammonia generation. (15th April 2022) - Fang, Jing; Xiong, Chuhao; Feng, Mingqian; Wu, Ye; Liu, Dong
Graphical abstract: Highlights: An integrated system based on chemical looping ammonia generation (CLAG) was proposed. The energy consumption and CO2 emissions of the proposed system was analyzed. The process achieved 6.88 GJ/tNH3 and 2.05 kg/kgNH3 CO2 emission. Abstract: Ammonia (NH3 ) has attracted much attention as both a fuel and an energy carrier due to its transportability and cleanliness. At present, most of NH3 is synthesized by the catalytic Haber-Bosch reaction ( N 2 + 3 H 2 ⇌ 2 N H 3 ). Due to its energy-intensive processes for hydrogen production, high carbon dioxide (CO2 ) emissions as well as high pressure required for NH3 synthesis, an alternative highly efficient system is needed. In this study, an integrated system based on chemical looping ammonia generation (CLAG), which combines air separation, N-sorption/desorption (ammonia synthesis), steam generation and urea production is proposed. The system employs a novel ammonia production loop and produces steam, carbon monoxide (CO) and urea as by-products. System modelling is conducted using Aspen Plus V11 (Aspen Technology, Inc.). The results showed the energy consumption can reach 6.88 GJ/tNH3 . The total CO2 emission of the ammonia synthesis system was 2.05 kg/kg NH3 in which direct CO2 emission dropped to 0.43 kg/kg NH3, and with urea production, the direct CO2 emission can reduce to −0.86 kg/kg NH3, leading to negative CO2 emissions.